Pemanfaatan Teknologi Digital dalam Pembelajaran Bahasa Arab: Kajian Literatur Terhadap Aplikasi dan Platform - Asfihani, Muhammad Lutfi; Al Anshori, Ahmad Zakariya; Hafidz, Muhammad; Efendi, Agus (AL-WARAQAH Jurnal Pendidikan Bahasa Arab, 2025)
The development of digital technology has changed the paradigm of Arabic language learning from conventional methods to a more interactive, adaptive, and data-driven approach. This article takes an in-depth look at the use of mobile applications such as Duolingo, Mondly, and Memrise, as well as Learning Management System (LMS) platforms such as Teachmint and Learning Al-Jazeera in Arabic language learning. This research uses a systematic literature review approach to national and international. The results of the analysis show that mobile applications are effective in building motivation and independent learning habits through gamification and micro-learning mechanisms, while LMS is superior in managing structured, collaborative, and assessment-based learning. Recent literature studies (Okumuş Dağdeler, 2023; Çobanoğullari & Özbek, 2025) also confirm that the integration of AI-powered chatbots and spaced repetition techniques can significantly improve vocabulary retention and speaking skills. However, teachers' limited digital literacy, shallow grammatical content, and unequal access to technology remain major challenges. This study confirms that collaboration between mobile applications and LMS can produce a more effective, contextual Arabic language learning model that is suited to the characteristics of the digital generation. Further research is recommended to evaluate the empirical application of these two media in the context of formal classrooms in Indonesia.